Hepatotoxicity of new oral anticoagulants: literature review - N. S. Popova; A. V. Philippova; T. L. Gakankin; A. S. Kolbin; A. R. Kasimova (Izdatelstvo OKI, 2019)
Tis article presents a literature review of hepatotoxicity of new oral anticoagulants which was obtained by diﬀerent methods options of pharmacovigilance. Te overview includes 35 information sources 24 articles, 4 methodic or regulatory guidelines, 3 expert group publications, 3 new drug application overviews and 1 source being clinical trial register search results. Upon the results of the literature review, it was concluded that pharmacovigilance methods analyzing data obtained within real world medical practice give more opportunities for safety signal management comparing to those analyzing only data obtained within randomized clinical trials.